Kinerja industri pengupasan, pembersihan dan sortasi kopi di Indonesia - Deassy Apriani; Imelda Imelda; Eka Rostartina (Department of Development Economics, Universitas Sriwijaya, 2017)
This study to investigate how the influence of production area and number of workers on coffee stripping production and how performance is seen in terms of economic efficiency and labor productivity levels with vulnerable time 2012-2017. This study uses a descriptive quantitative approach with panel data regression model. The findings of the study indicate that the production area and number of workers in the stripping, cleaning and sorting industries of coffee significantly affected the amount of coffee production in Indonesia. The efficiency values in the stripping, cleaning and sorting industries of coffee during 2012-2017 tends to be inefficient because the value of efficiency obtained is 0.26, which means that <1, while labor productivity in the stripping, cleaning, and coffee sorting industries have the average value is 62.24 percent per year. The level of labor productivity is influenced by the increase and reduction in the number of workers followed by an increase and decrease in the value of output.